An Iron Age ceramic sequence from the Bayt Bin Ati, al‐Ain, UAE. (22nd April 2019) - Power, Timothy; Benoist, Anne; Sheehan, Peter
Abstract: Rescue excavations associated with the adaptive reuse of a historic building in the Qattara Oasis revealed a 5 m stratigraphic sequence spanning the past 3000 years. The main period of occupation—roughly half the sequence—belongs to the Iron Age II and III periods ( c .1100–300 BC). Evidence of agriculture and industry was found which complements our understanding of the well‐known Iron Age settlements of al‐Ain. The present paper sets out the stratigraphic sequence and presents the phased ceramic assemblage, before considering the broader implications for the archaeology of Iron Age south‐east Arabia.